Pemberdayaan Komunitas Sebagai Strategi Penguatan Ketahanan Ekonomi Lokal: Implikasi pada Program Koperasi Merah Putih - Puji Nur Ekowati; Ravyansah Ravyansah (J-Coop : Journal of Co-operative, 2026)
The gap between rural and urban areas in Indonesia is evident in disparities in income, infrastructure, and human resource quality between the two regions. Accelerating the achievement of Indonesia Emas 2045 places economic transformation as a key sector. Active community participation is needed to achieve equitable economic strengthening, maximize innovation and productivity, optimize the use of science and technology, and achieve sustainable economic activities. This study examines the implementation of the Koperasi Merah Putih Program and community empowerment as a strategy to strengthen local economic resilience. This research employed a qualitative approach, including a literature review and policy analysis, focusing on community empowerment, strategies to increase local economic resilience, and the Koperasi Merah Putih Program. Cooperatives serve not only economic functions but also social functions based on the principle of family. Economic empowerment through the involvement of local communities can provide opportunities to manage local resources. Koperasi Merah Putih is one of the national strategic programs based on a people’s economy with the aim of achieving prosperity. Cooperatives are expected to be a driving force for the economy, supporting the achievement of local economic resilience.